Stabilized Sewage Sludge as Fertilizer: Risks Related to the Presence of Microplastics - Jagoda Worek; Kamil Kawoń; Joanna Chwiej; Katarzyna Styszko (Applied Sciences, 2025)
Microplastics are an increasingly concerning environmental pollutant. Their presence in agricultural settings is particularly troubling due to their persistence and potential to infiltrate soil, groundwater, and the food chain. This study focused on analyzing fertilizer derived from stabilized sewage sludge collected in June and July. The average mass of microplastics isolated per 100 g of fertilizer was 461.28 mg in June and 458.92 mg in July. The analysis revealed a substantial quantity of microplastics, with fragments and fibers being the predominant forms. In the June samples, an average of 860 microplastic particles was detected, compared to 734 in July (507 fragments and 227 fibers). The most common particle sizes in June ranged from 1500 to 2000 µm and 2000 to 2500 µm, with a significant proportion also exceeding 4000 µm. In July, particles larger than 4000 µm were the most prevalent. Qualitative analysis using Raman microscopy identified polyethylene—a widely used, inexpensive, and chemically stable polymer—as one of the main types of plastic present.